1997
DOI: 10.1038/hdy.1997.169
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing rates of individual Mimulus ringens genets are correlated with anther–stigma separation

Abstract: Anther-stigma separation (herkogamy) is highly variable within populations of Mimulus ringens, a bumblebee-pollinated perennial herb with a mixed-mating system. The relationship between this floral trait and individual outcrossing rates was studied in two experimental populations composed of genets with unique multilocus combinations of homozygous genotypes. This facilitated determination of individual outcrossing rates through unambiguous assignment of paternity to all 1560 sampled progeny. In each population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 48 publications
3
103
2
Order By: Relevance
“…We have emphasized the effect of mating system on floral evolution, but the mating system is itself dependent on the characters considered in this study. Stigmaanther separation may often determine the amount of self-fertilization that occurs within a flower (Vasek, 1965;Robertson and Lloyd, 1991;Karron et al, 1997), although several studies of M. guttatus have failed to find a relationship Arathi et al, 2002). Corolla size (width and length) can influence the mating system by affecting the 'attractiveness' of flowers to pollinators (Galen et al, 1987) and thus the amount of foreign pollen that a plant is likely to receive (or to be visited at all).…”
Section: Discussionmentioning
confidence: 99%
“…We have emphasized the effect of mating system on floral evolution, but the mating system is itself dependent on the characters considered in this study. Stigmaanther separation may often determine the amount of self-fertilization that occurs within a flower (Vasek, 1965;Robertson and Lloyd, 1991;Karron et al, 1997), although several studies of M. guttatus have failed to find a relationship Arathi et al, 2002). Corolla size (width and length) can influence the mating system by affecting the 'attractiveness' of flowers to pollinators (Galen et al, 1987) and thus the amount of foreign pollen that a plant is likely to receive (or to be visited at all).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a significant difference in the mean outcrossing rates of the two herkogamy classes is surprising for two reasons. First, most other studies that considered herkogamy variation among individuals found significantly diminished outcrossing in low-herkogamous individuals (e.g., Karron et al 1997;Brunet and Eckert 1998;Takebayashi et al 2006;Herlihy and Eckert 2007). Second, the absolute amount of herkogamy difference between classes was shown to greatly affect seed set under pollinator exclusion , demonstrating that the autonomous component of selfing is affected by herkogamy.…”
Section: Effects Of Herkogamy On Matingmentioning
confidence: 94%
“…In self-compatible species, herkogamy has been mainly proposed as a mechanism to limit selfing, but it also influences sexual interference between male and female floral functions (Barrett 2002). Herkogamy negatively affects seed set when pollinators are absent (e.g., Luijten et al 1999;Moeller 2006;de Vos et al 2012), and several genetic analyses confirmed the expected positive correlation between herkogamy and outcrossing rates, both among (e.g., Rick et al 1977;Holtsford and Ellstrand 1992;Luo and Widmer 2013) and within populations (e.g., Karron et al 1997;Brunet and Eckert 1998;Takebayashi et al 2006;Herlihy and Eckert 2007;Weber et al 2012; but see Medrano et al 2005Medrano et al , 2012. Importantly, herkogamy is known to decrease during anthesis in some species, potentially increasing opportunity for autonomous selfing in later stages of anthesis (Luijten et al 1999;Armbruster et al 2002;Duan et al 2010;de Vos et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Differences between populations in the mean flower size of hermaphrodites may affect pollination success (through influence on pollinator attractiveness) and mating system parameters. Anther-stigma separation, a parameter known to influence outcrossing rates in other self-compatible plants (Karron et al, 1997;Chang and Rausher, 1998), is directly related to corolla tube length in D. laureola.…”
Section: Study Sitesmentioning
confidence: 99%